2020
DOI: 10.1111/liv.14608
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus eradication by direct antiviral agents abates oxidative stress in patients with advanced liver fibrosis

Abstract: Background and aims: HCV eradication improves non-hepatic outcomes such as cardiovascular diseases, although without clearly defined mechanisms. In this study we aimed to assess whether improvement of carotid atherosclerosis may be linked to a reduction in systemic oxidative stress after viral clearance. Methods: We studied a retrospective cohort of 105 patients (age 62.4 ± 11.2 years; 62 men) with F3/F4 fibrosis, characterized by carotid ultrasonography at baseline and at sustained virologic response (SVR) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…In particular, available studies concerning the effects of DAA treatments on glucose control in T2DM subjects are not only numerically limited but also divergent from each other 12‐14 . Indeed, the studies performed so far in this field have demonstrated several limitations including short‐term follow‐up and lack of information on possible differences related to the degree of the liver damage in the DAA‐treated patients 15‐17 . The aims of this study were to evaluate whether the DAA‐based HCV cures may have an effect on long‐term glucose control in T2DM patients and whether this possible effect might be influenced by the grade of severity of the liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, available studies concerning the effects of DAA treatments on glucose control in T2DM subjects are not only numerically limited but also divergent from each other 12‐14 . Indeed, the studies performed so far in this field have demonstrated several limitations including short‐term follow‐up and lack of information on possible differences related to the degree of the liver damage in the DAA‐treated patients 15‐17 . The aims of this study were to evaluate whether the DAA‐based HCV cures may have an effect on long‐term glucose control in T2DM patients and whether this possible effect might be influenced by the grade of severity of the liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…DAA treatment was also beneficial to control blood sugar in liver transplant recipients with recurrent HCV 45 . Furthermore, Salomone et al 46 confirmed that HCV‐infected patients were in oxidative stress, and antiviral therapy ameliorated the state of oxidative stress, which might be involved in the improvement of atherosclerosis. Therefore, it seems plausible that antiviral therapy for HCV may reduce the risk of CVD.…”
Section: Discussionmentioning
confidence: 97%
“…The advent of DAAs has led to a significant reduction of the risk of cardiovascular events [158][159][160][161], and this strong clinical impact is still maintained even when potential confounders such as liver fibrosis are considered [162,163]. This effect is probably due to the decrement in atherosclerosis as reported by Italian authors in [164][165][166].…”
Section: Cardiovascular Diseasesmentioning
confidence: 91%